Representasi Kemiskinan dan Kelas Sosial dalam Naskah Drama “Kapai-Kapai” Karya Arifin C. Noer: Kajian Sosiologi Sastra - Farahdila, Nonika; Mulyono, Mulyono; Qomariyah, Uum (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
The purpose of this study is to describe the representation of poverty and social class in the play “Kapai-Kapai” by Arifin C. Noer through literary sociology studies. Noer through literary sociology study. The method used in this research is descriptive qualitative. The data source in this research is the play “Kapai-Kapai” by Arifin C. Noer and references in the form of articles or books. Noer and references in the form of related articles or books. The method of data collection is done by literature study with the technique of simak catat. Data analysis was carried out with descriptive analysis in the form of selecting quotations in the form of dialogue between characters, monologues, and narratives that are relevant to the focus of research, presenting data to facilitate identification and then drawing conclusions based on the study of literary sociology theory. The results showed that the play “Kapai-Kapai” by Arifin C. Noer presents a picture of power relations between characters. Noer presents a picture of power relations between laborers and employers as a symbol of inequality and social class. The poverty that ensnares Abu's character makes him seek illusions and commit acts of cruelty with Iyem, his wife. This shows that poverty is not just an individual problem, but also the result of a social system that places certain groups in a marginalized position. Thus, literary works function as a reflective medium that raises social class issues and invites readers to reflect on the condition of society.